U.S. export controls and economic sanctions - Hirschhorn, Eric L.; Krauland, Edward J.; Egan, Brian James 1972- (Oxford University Press, 2022)
This book is a must for those who deal with United States government export control and economic sanctions regulations. Written as a user's manual rather than an academic or historical treatise, it covers in considerable detail-but in language that is intelligible to non-lawyers as well as lawyers-the Commerce Department's controls on exports of commercial, "dual-use" (having both commercial and military utility), and low-level military items, the State Department's controls on higher-level military items, the Treasury Department's approximately thirty different economic sanctions programs, the Nuclear Regulatory Commission's controls on nuclear-related commodities, and the Energy Department's restrictions on assistance to foreign nuclear programs. Given the authors' decades of experience with these regulations, the book not only explains the legal rules but also offers tips-not necessarily reflected in the regulations themselves-about how to interpret the regulations and deal with the regulators"--